Mrs. Everything : a novel - Weiner, Jennifer (Atria Books, 2019)
"A smart, thoughtful, and timely exploration of two sisters' lives from the 1950s to the present as they struggle to find their places--and be true to themselves--in a rapidly evolving world. Mrs. Everything is an ambitious, richly textured journey through history--and herstory--as these two sisters navigate a changing America over the course of their lives"--